Dispersive Solid Phase Extraction for the Analysis of Veterinary Drugs Applied to Food Samples: A Review. (18th October 2017) - Islas, Gabriela; Ibarra, Israel S.; Hernandez, Prisciliano; Miranda, Jose M.; Cepeda, Alberto
Abstract : To achieve analytical success, it is necessary to develop thorough clean-up procedures to extract analytes from the matrix. Dispersive solid phase extraction (DSPE) has been used as a pretreatment technique for the analysis of several compounds. This technique is based on the dispersion of a solid sorbent in liquid samples in the extraction isolation and clean-up of different analytes from complex matrices. DSPE has found a wide range of applications in several fields, and it is considered to be a selective, robust, and versatile technique. The applications of dispersive techniques in the analysis of veterinary drugs in different matrices involve magnetic sorbents, molecularly imprinted polymers, carbon-based nanomaterials, and the Quick, Easy, Cheap, Effective, Rugged, and Safe (QuEChERS) method. Techniques based on DSPE permit minimization of additional steps such as precipitation, centrifugation, and filtration, which decreases the manipulation of the sample. In this review, we describe the main procedures used for synthesis, characterization, and application of this pretreatment technique and how it has been applied to food analysis.